DIFFERENT APPROACHES TO THE INTERPRETATION OF THE CONCEPT OF "PEDAGOGICAL PROFESSIONALISM" IN SCIENTIFIC RESEARCH - Dolgaya, Н. В.; Dudnik, Н. Ю. (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the problem of variuos theoretical approaches to the definition of the notion "pedagogical professionalism" and its contents.